β-Amino functionalization of cinnamic Weinreb amides in ionic liquid - Wang, Yi-Ning; Sun, Guo-Xiang; Qi, Gang (Beilstein Journal of Organic Chemistry, 2016)
2-Ns-Protected β-amino Weinreb amides were synthesized by aminochlorination of α,β-unsaturated Weinreb amides in an ionic liquid, 1-n-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([BMIM][NTf2]). Processed without the use of metal catalysts or the need of an inert gas atmosphere, the presented process can be readily performed as a one-pot synthesis at room temperature. Moreover, the preparation has the distinct advantages of the use of 2-NsNCl2 as an inexpensive and stable nitrogen/halogen source and the ionic liquid as a recyclable reaction media. Nine examples were examined, and modest to good isolated chemical yields (40–83%) were obtained.
Keywords: aminochlorination; β-amino functionalization; ionic liquid; Weinreb amides